Mutations in Flavobacterium johnsoniae gldF and gldG Disrupt Gliding Motility and Interfere with Membrane Localization of GldA - Hunnicutt, David W. (American Society for Microbiology, 2002)
Flavobacterium johnsoniae moves rapidly over surfaces by a process known as gliding motility. The mechanism of this form of motility is not known. Four genes that are required for F. johnsoniae gliding motility, gldA, gldB, gldD, and ftsX, have recently been described. GldA is similar to the ATP-hydrolyzing components of ATP binding cassette (ABC) transporters. Tn4351 mutagenesis was used to identify two additional genes, gldF and gldG, that are required for cell movement. gldF and gldG appear to constitute an operon, and a Tn4351 insertion in gldF was polar on gldG. pMK314, which carries the entire gldFG region, restored motility to each of the gldF and gldG mutants. pMK321, which expresses GldG but not GldF, restored motility to each of the gldG mutants but did not complement the gldF mutant. GldF has six putative membrane-spanning segments and is similar in sequence to channel-forming components of ABC transporters. GldG is similar to putative accessory proteins of ABC transporters. It has two apparent membrane-spanning helices, one near the amino terminus and one near the carboxy terminus, and a large intervening loop that is predicted to reside in the periplasm. GldF and GldG are involved in membrane localization of GldA, suggesting that GldA, GldF, and GldG may interact to form a transporter. F. johnsoniae gldA is not closely linked to gldFG, but the gldA, gldF, and gldG homologs of the distantly related gliding bacterium Cytophaga hutchinsonii are arranged in what appears to be an operon. The exact roles of F. johnsoniae GldA, GldF, and GldG in gliding are not known. Sequence similarities of GldA to components of other ABC transporters suggest that the Gld transporter may be involved in export of some material to the periplasm, outer membrane, or beyond.